A survey to assess the availability, implementation rate and remuneration of pharmacist-led cognitive services throughout Europe - Soares, Inês Branco (2019)
Background: Pharmacist-led cognitive services (PLCS) are increasingly necessary in primary care as a response to patient-centered care. However, the implementation rate and remuneration models of PLCS are either absent or superficially described in the literature. Objective: The aim of this study is to review the implementation of PLCS in primary care across Europe and explore the associated third-party paid remuneration models. Methods: A cross-sectional study was conducted using an online survey sent to representatives of 44 European countries. The survey listed 21 PLCS and asked respondents to report the availability of the service, the rate of implementation and the existence of remuneration. To ensure credible data, data triangulation was sought using three representatives per country, representing backgrounds of community pharmacy, pharmacy practice research and health policy. Subsequently, data was validated, and consensus sought. Results: Data were collected between November 2016 and October 2017 from 34 different countries across Europe (79%). Provision of medicines’ information (94.1%), generic substitution (85.3%), provision of emergency oral contraception (70.6%) and point-of-care testing (67.7%) were the services reported as the most widely disseminated in European primary care. Medication review was the most disseminated among advanced services (55.9%). Medication review, adherence support and monitoring, prescription renewal, opioid substitution and travel medicine had the highest implementation rates reported. Half of the participating countries mentioned models of remuneration, predominantly based on a fee-for-service, with less frequent reports of pay-for-performance or mixed models of remuneration. Conclusions: The availability of PLCS is increasing and varying in scope across Europe. There is wide variation in the implementation level of services across Europe and a lack of valid data. Remuneration of PLCS is also spreading but no clear pattern was found that relates service provision to payment.